The pH signalling transcription factor PacC modulate growth, development, stress response and pathogenicity of Trichothecium roseum. (23rd February 2022) - Wang, Bin; Han, Zhanhong; Gong, Di; Xu, Xiaobin; Li, Yongcai; Sionov, Edward; Prusky, Dov; Bi, Yang; Zong, Yuanyuan
Summary: pH is one of the important environmental factors that affect the growth, development and pathogenicity of postharvest pathogen. The transcription factor PacC dominates the pH signal pathway. PacC in Trichothecium roseum showed three typical conserved zinc finger domains and closest homology to Fusarium graminearum . T. roseum increased the environmental pH both in vitro and in vivo . Expression patterns of TrpacC under different pH showed that at increasing pH from 3 to 5, the wild‐type (WT) strain induced the expression of TrPacC in parallel to increased fungal growth; however, TrPacC expression decline at higer pH than 5, while fungal growth continued to increase. Development of a Δ TrPacC mutant down‐regulated the expression of TrbrlA, TrabaA and TrwetA, reduced sporulation and delayed spore germination, resulting in smaller spores and sparse hyphae. Δ TrPacC mutant was sensitive to ionic stress, oxidative stress and cell wall integrity stress compared to the WT strain, especially the ionic stress. In addition, ∆ TrPacC mutant showed reduced pathogenicity to muskmelon and tomato fruits. Taken together, T. roseum is an alkalinizing fungus, and the acidic environment could induce TrPacC expression. TrPacC positively regulates fungal growth and development as well as pathogenicity showing effect on fungal response to different stresses.